1980
DOI: 10.1002/1097-0142(19801115)46:10<2179::aid-cncr2820461014>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative radiotherapy for advanced carcinoma of the biliary system

Abstract: Since November 1973, intraoperative radiotherapy has been performed on five patients with unresectable, advanced carcinoma of the bile duct at the hepatic hilus and six patients with unresectable carcinoma of the gallbladder. A treatment cone with a diameter ranging from 4--10 cm was directly applied at the lesion. A single dose of 2500--3000 rad with 11 to 20 meV electrons was delivered. In all patients, recanalization of the obstructed bile duct was observed by the postoperative cholangiography. The local ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

1984
1984
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(18 citation statements)
references
References 10 publications
0
15
0
3
Order By: Relevance
“…New rudiation modalities: The use of intraoperative electrons has been reported for unresectable lesions by several Japanese groups, most recently by Todorki et al 33 Although early bile duct recanalization was observed, regional recurrence occurred in the vast majority suggesting that tumor had extended beyond the small volume encompassed by the intraoperative cones (no external irradiation was used).…”
Section: Treatmentmentioning
confidence: 99%
“…New rudiation modalities: The use of intraoperative electrons has been reported for unresectable lesions by several Japanese groups, most recently by Todorki et al 33 Although early bile duct recanalization was observed, regional recurrence occurred in the vast majority suggesting that tumor had extended beyond the small volume encompassed by the intraoperative cones (no external irradiation was used).…”
Section: Treatmentmentioning
confidence: 99%
“…The experience reported by Abe 1,3 did not show any significant improvement of survival rates with IORT compared to external postoperative irradiation. Encouraging results were reported by Todoroki 55 using preoperative radiotherapy combined with IORT in advanced biliary carcinoma: the 1-year survival rate was 63%. A more recent study of Tsukuba University in Japan 56 in stage IVA Klatskin tumour showed that adjuvant radiotherapy including IORT yielded significantly higher 5-year survival rates (33.9%) than in the resection alone group (13.5 %).…”
Section: Biliary Tract Cancermentioning
confidence: 86%
“…The evidence would not support standard use of either modality. There are similarly limited datasets describing the use of brachytherapy 29 , 30 , intraoperative radiation 31 and chemoradiation 32 , 33 . The conclusion is that RT should only be considered in the context of a clinical trial.…”
Section: Therapeutic Optionsmentioning
confidence: 99%